(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2014)
Porokeratosis is a clonal disorder of epidermal keratinization, which is characterized by hyperkeratotic papules or plaques that are surrounded by a thread-like elevated border. The histopathologic hallmark of porokeratosis is the cornoid lamella, which is a thin column of parakeratosis that overlies a thin or absent granular layer and that corresponds to the raised, hyperkeratotic border. Porokeratosis has five clinical types and malignant degeneration has been described in all forms of porokeratosis. We report a forty five year old farmer with a large plaque in chest for 30 years and multiple nodules within the large plaque for 2 years. A section of skin from margin of the plaque reveals histopathological features of porokeratosis and section from nodules reveals an invasive squamous cell carcinoma. To the best of our knowledge, this is the first reported case of porokeratosis transformed to squamous cell carcinoma on Bangladesh. DOI: http://dx.doi.org/10.3329/jbcps.v32i1.21035 J Bangladesh Coll Phys Surg 2014; 32: 31-36